Rational design and synthesis of 3-heteroaromatics coumarin molecules with unusual solution and solid dual efficient luminescence. Issue 21 (24th May 2019) - Zhou, Zi-chun; Zheng, An-na; Cui, Yan-hong; Lin, Zhang-qi; Niu, Wen-jie; Zhang, Yong-jian; Gao, Jian-rong; Li, Yu-jin
Abstract: 3-Imidazolyl coumarin molecules were synthesized under solvent-free condition and the optical properties both in solution and the solid state were determined. The compounds showed dual efficient luminescence, which were blue fluorescence with the highest fluorescence quantum yield being more than 0.9 and also exhibited favorable yellow solid-state fluorescence. Additionally, by using density functional theory (DFT) and time-dependent DFT (TD-DFT) calculation, all structures were optimized and the associated optical performances showed similar results as the experimental results. Graphical abstract: Image 1